Can Tho, Vietnam : Enhancing Urban Resilience - World Bank Group (Washington, DC, 2014)
Cities are vulnerable to many types of shocks and stresses, including natural hazards like storms and sea level rise, but also man-made ones like economic transformation and rapid urbanization. These shocks and stresses have the potential to bring city systems to a halt and reverse years of socio-economic development gains. Cities that are to grow and thrive in the future must take steps to address these shocks and stresses. Simply put, a resilient city is one that can adapt to these types of changing conditions and withstand shocks while still providing essential services to its residents. A resilient city can keep moving toward its long-term goals despite the challenges it meets along the way. The residents of Can Tho are familiar with challenges the city is dealing with chronic seasonal flooding, periodic flood disasters, riverbank erosion, saltwater intrusion, possible land subsidence, economic transition, and rapid urbanization. The city is also aware of challenges that lay on the horizon like sea level rise, a labor force that is unprepared for high technology industry, and an urban population that expects high-quality urban infrastructure and services from its government. These challenges are interlinked encroachment on canals and riverbeds increases flood risk, while flooding and rampant growth impacts the safety and quality of life in urban areas.